Assessing the Effectiveness of Public Research Institutions : Fostering Knowledge Linkages and Transferring Technology in Malaysia - World Bank (World Bank, Kuala Lumpur, 2020)
The transition to a more innovation-based growth model is even more urgent in the current uncertain global context[1]. While the GDP growth rate has proven resilient in recent years, declining oil and gas output, coupled with economic shocks, including the recent COVID-19 pandemic, havedented the growth momentum. In this difficult context, a sustained increase in private investment, coupled with improvements in productivity willbe necessary to maintain a sustainable economic growth trajectory that enables Malaysia to reach high-income status. There is a significant body ofevidence to demonstrate a positive correlation between levels of innovation and productivity. Malaysia recognizes the need to embrace an innovation-driven growth model to weather the current global crisis and achieve its aspirations of becoming a high-income nation. Malaysia hastransformed what was once an agricultural economy, to one that is manufacturing-led. Recognizing the importance of productivity led growth model,research and development (R&D) resources and expenditures in Malaysia grew over the years as did policy efforts through reforms and improvements to bolster educational as well as science, technology and innovation capabilities and outcomes.